Pandemic shock and regional economic resilience in Indonesia: A linear mixed model - Novalia; Bima Ramadhan; Kenny Candra Pradana; Ahmad Naqiyuddin Bakar; Surachman Surjaatmadja (FoundAE, 2026)
Background: The COVID-19 pandemic has emerged as a major non-traditional security threat, generating substantial economic disruptions and destabilizing labor markets worldwide. In Indonesia, the surge in open unemployment during the pandemic has raised concerns regarding regional economic resilience and its broader implications for national economic security. As unemployment can exacerbate social vulnerability and weaken adaptive capacity, understanding regional labor market dynamics is critical for strengthening national resilience. Aims: This study aims to examine the impact of pandemic-induced shocks on provincial open unemployment rates in Indonesia and assess regional heterogeneity in economic resilience. Method: The study employs provincial level panel data and applies a Linear Mixed Model (LMM) to capture both temporal effects and regional heterogeneity. The model incorporates pandemic indicators alongside structural economic variables, including informal employment and commodity distribution dynamics, to evaluate their roles as vulnerability factors or resilience buffers during the crisis period. Results: The findings show that the COVID-19 pandemic has significantly increased the open unemployment rate in all provinces in Indonesia. This study also shows that the percentage of trade and transportation margins (MTT) for shallots influences the open unemployment rate with a p-value of 0.017 and a variable coefficient of 0.021. In addition, it was also found that the proportion of informal workers in the total national workforce also has a significant effect on changes in the open unemployment rate (p-value: 0.001, coefficient: -0.077). Another finding from this study is that the level of high school education does not have a significant effect on the open unemployment rate. Conclusion: This study on pandemic induced unemployment shocks contributes by integrating regional heterogeneity into economic resilience analysis using a multilevel modeling framework. Strengthening regional economic resilience through labor market flexibility, supply chain stability, and adaptive policy coordination is essential to safeguarding socioeconomic stability and reinforcing Indonesia’s national resilience against large-scale non-traditional threats.